Copulatory behaviour and seminal parameters of rapid ejaculator rats during competition and female pacing. Issue 3 (4th May 2023) - Fuentes-Morales, María R.; Fernández-Guasti, Alonso; Juárez, Margarita; Lucio, Rosa A.
Abstract : Axioms of sperm competition theory (risk and intensity model) predict that males increase sperm expenditure when ongoing competitive copulating encounters with other males. Particularly, the intensity model that considers a real male confrontation has not been experimentally tested in laboratory rats. Furthermore, no study has explored the active role of the female (that occurs in natural conditions) in regulating the timing of copulation on the effects of competition on sexual behaviour and seminal parameters. Thus, the goal of this study was to analyse the copulatory behaviour and seminal parameters under male–male competition and female pacing. In order to control for possible variations due to the sexual behaviour phenotype, all experiments were done in male rats with short ejaculation latencies (rapid ejaculators). The results show that competition decreased by half the ejaculation latency and increased sperm quantity, but substantially decreased sperm motility. On the contrary, when competition is tested under conditions where the female regulates the timing of copulation (paced mating), the ejaculation latency increased to double, the sperm count did not change, and the sperm motility significantly decreased. The variations in the parameters of the ejaculate depend on the context, i.e., the confrontation with a competitor, and the active participation of the female during copulation. Probably, when there is more than one male during mating, the female – through cryptic choice – promotes mechanisms that interfere temporally with sperm motility. HIGHLIGHTS: Copulatory competition shortens the ejaculation latency of rapid ejaculators. Copulatory competition plus female pacing lengthens the ejaculation latency of rapid ejaculators. Sperm motility drastically decreases due to competition regardless of female pacing. Sperm count increases during competition but not under competition plus female pacing. Seminal plug's size and weight do not change despite competition and female pacing.